1987
DOI: 10.1021/bi00381a004
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodinated, photoactivatable phosphatidylcholine and phosphatidylserine: transfer properties and differential photoreactive interaction with human erythrocyte membrane proteins

Abstract: An isotopically labeled cross-linking reagent, succinimido 3-(3-[125I]iodo-4-azidophenyl)propionate, has been synthesized and coupled to 1-acyl-2-(aminocaproyl)phosphatidylcholine according to previously described procedures [Schroit, A. J., & Madsen, J. (1983) Biochemistry 22, 3617-3623]. 125I- and N3-labeled phosphatidylserine (125I-N3-PS) was produced from the phosphatidylcholine (PC) analogue by phospholipase D catalyzed base exchange in the presence of L-serine. These phospholipid analogues are photoactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…The experiments in the present study demonstrate the use of a hydrophobic photoaffinity probe for covalent labeling of (27). These agents inhibit labeling of the proteins by probe diffusion through the aqueous phase.…”
Section: Discussionmentioning
confidence: 68%
“…The experiments in the present study demonstrate the use of a hydrophobic photoaffinity probe for covalent labeling of (27). These agents inhibit labeling of the proteins by probe diffusion through the aqueous phase.…”
Section: Discussionmentioning
confidence: 68%
“…A striking common feature is the PS requirement for a full activity expressed by the erythrocyte (this work), the coated vesicle [18] or the chromaffin granule Mg-ATPase (G.M., unpublished data). Labeling by ATP- [7)SS] confirmed that the apparent molecular weight of the erythrocyte Mg-ATPase, determined by electrophoresis under denaturating and reducing conditions, is in the 115-120 kDa range [11]. The labeling of that band is abolished under conditions where the ATPase is inactive, i.e.…”
Section: Discussionmentioning
confidence: 89%
“…However, the enzyme displays an absolute requirement for the stereochemistry of the glycerol backbone; the sn -2,3-glycerol analog of the naturally-occurring sn -1,2-glycero-lipid is not a substrate for transport (72,80). In contrast to the polar headgroup specificity, the flippase is capable of accepting PS molecules containing fatty acids of various lengths and composition, including spin, fluorescent, and photoactivatable groups (25,55,58,59,63,(89)(90)(91), but prefers reporter groups attached to longer acyl chains (58, 59). Using an endocytosis mutant, Nichols recently demonstrated a similar ATP-dependent transport activity in yeast, although NBD-PC was transported in addition to NBD-PE (92,93).…”
Section: Flippasesmentioning
confidence: 99%